De Novo sphingolipid synthesis is essential for Salmonella-induced autophagy and human beta-defensin 2 expression in intestinal epithelial cells. Issue 1 (December 2016) - Huang, Fu-Chen
Abstract Background Sphingolipids are important for innate immune response to eliminate infected pathogens and involved in autophagy. On the other hand, nucleotide-binding oligomerization domain-containing protein 2 (NOD2) served as an intracellular pattern recognition receptor to enhance host defense by inducing autophagy and the production of antimicrobial peptides, such as human beta-defensin-2 (hBD-2). However, the role of sphingolipids inSalmonella -induced autophagy and hBD-2 response in intestinal epithelial cells has not been previously elucidated. Methods Salmonella typhimurium wild-type strain SL1344 was used to infect SW480, an intestinal epithelial cell. hBD-2 and interleukin-8 (IL-8) mRNA expressions were assessed in SW480 cells using RT-PCR, and intracellular signaling pathways and autophagy protein expression were analyzed by Western blot in SW480 cells in the presence or absence of inhibitors or transfected with siRNA. Results We demonstrated that inhibition ofde novo sphingolipid synthesis repressed the membrane recruitment of NOD2 and autophagy-related protein 16-like 1 (Atg16L1), suppressedSalmonella -induced autophagic protein LC3-II expression, and reduced NOD2-mediated hBD-2 response inSalmonella -infected SW480 cells. Contrasting to the utilization of membrane cholesterol on maintenance ofSalmonella -containing vacuoles and anti-inflammation bySalmonella, sphingolipids act on epithelial defense against the invasive pathogen. Conclusions Our results offer mechanistic insights on the role ofde novo sphingolipid synthesis in the innate immunity of intestinal epithelial cells toSalmonella infection. The pharmaceuticals enhancing or diet enriched with sphingolipids may induce the dual anti-bacterial mechanisms. The role ofde novo sphingolipid synthesis on inflammatory bowel disease is deserved to be further investigated.